Chronic traumatic encephalopathy and other neurodegenerative proteinopathies - Tartaglia, Maria C.; Hazrati, Lili-Naz; Davis, Karen D.; Green, Robin E.; Wennberg, Richard; Mikulis, David; Ezerins, Leo J.; Keightley, Michelle; Tator, Charles (Frontiers in Human Neuroscience, 2014)
“Chronic traumatic encephalopathy” (CTE) is described as a slowly progressive neurodegenerative disease believed to result from multiple concussions. Traditionally, concussions were considered benign events and although most people recover fully, about 10% develop a post-concussive syndrome with persisting neurological, cognitive and neuropsychiatric symptoms. CTE was once thought to be unique to boxers, but it has now been observed in many different athletes having suffered multiple concussions as well as in military personal after repeated blast injuries. Much remains unknown about the development of CTE but its pathological substrate is usually tau, similar to that seen in Alzheimer’s disease and frontotemporal lobar degeneration. The aim of this “perspective” is to compare and contrast clinical and pathological CTE with the other neurodegenerative proteinopathies and highlight that there is an urgent need for understanding the relationship between concussion and the development of CTE as it may provide a window into the development of a proteinopathy and thus new avenues for treatment.